Diabetes-Care Quality among Veterans in Southwest Indiana, United States - Kaur, Harsimran; Sood, Aayushi; Sandhu, Devkarn; Bhatia, Vishal (Journal of Social Health and Diabetes, 2019)
Objective Diabetes is more prevalent among U.S. veterans than the general population. The study is among the U.S. veterans in Southwest Indiana with diabetes mellitus type 2 to understand their demographics, comorbidities, and complications that could help guide strategies to address the prevalence of diabetes among U.S. veterans in the area. Previous diagnosis and referral to the specialty clinics approaches are needed to lower the prevalence of diabetes among U.S. veterans and preventing diabetes-related complications to improve their health status.Method We constructed a retrospective study of veterans in the Southwest area with medically treated diabetes type 2, who received Veterans Health Administration primary care and were referred to our specialty clinic. We categorized based on demographics, comorbidities, initial HbA1c percentage, and complications, and created multivariable models.Results In our study of 80 U.S. veterans with diabetes, 90% had comorbidities already when they presented to our clinic. Diabetes was more prevalent in patients older than 60 years. Around 60% of patients presented with complications such as neuropathy, coronary arterial disease, and heart problems. We calculated the HbA1c when the patients came, and around 42% had hemoglobin A1c (HbA1c) over 10%. Patients with exposure to Agent Orange during the Vietnam War had HbA1c over 9%.Conclusion U.S. veterans with diabetes type 2 referred to the specialty clinic have high HbA1c and more complications on their first visit. Therefore, veterans need to be referred early to the specialty clinics during the course to improve their health status. Mission’s Act 2019 empowers veterans with increased access to community care.
Keywords: diabetes mellitus type 2; mission act 2019; veterans